Counting Enhances Kindergarteners’ Mappings of Number Words Onto Numerosities - Chan, Winnie Wai Lan (Frontiers in Psychology, 2020)
We can make sense of how many a number represents by mapping the symbolic number word system onto the nonsymbolic, approximate number system. This study adopted an intervention design to examine whether counting is essential in driving the formation of such symbolic-nonsymbolic mappings. We compared kindergarteners’ mapping ability after reading stories (1) without cardinal labels, or (2) with cardinal labels, or (3) with cardinal labels and verbal counting. Results showed that children who had counted when reading the stories showed better mapping between number words and their approximate representations than their peers in the other two conditions – suggesting that counting plays a role in developing early symbolic-nonsymbolic mappings. Such findings provides empirical support for parents and early educators to enhance young children’s mappings between numbers words and approximate representations through counting activities – such as counting the items in the story books while reading to children.